Has the health professions education research agenda changed in the new millennium - Vanessa Burch (South African Medical Association, 2015)
One of the key mandates of the 21st century is the provision of comprehensive, integrated healthcare to all members of society. For this to become a reality the training needs of all healthcare professionals must be addressed by the research endeavours of health professions educators. So, the key question is, â€˜Does the current health professions education research agenda address the training needs of all healthcare professionals?â€™.Â